Electron-enriched thione enables strong Pb–S interaction for stabilizing high quality CsPbI3 perovskite films with low-temperature processing. Issue 12 (27th February 2020) - Xu, Xiaojia; Zhang, Hao; Li, Erpeng; Ru, Pengbin; Chen, Han; Chen, Zhenhua; Wu, Yongzhen; Tian, He; Zhu, Wei-Hong
Abstract : A neutral molecular additive of 4(1 H )-pyridinethione (4-PT) is used for growing high quality black-phase CsPbI3 thin films at low temperatures. Abstract : Cesium lead iodide (CsPbI3 ) perovskite is a promising photovoltaic material with a suitable bandgap and high thermal stability. However, it involves complicated phase transitions, and black-phase CsPbI3 is mostly formed and stabilized at high temperatures (200–360 °C), making its practical application challenging. Here, for the first time, we have demonstrated a feasible route for growing high quality black-phase CsPbI3 thin films under mild conditions by using a neutral molecular additive of 4(1 H )-pyridinethione (4-PT). The resulting CsPbI3 thin films are morphologically uniform and phase stable under ambient conditions, consisting of micron-sized grains with oriented crystal stacking. With a range of characterization experiments on intermolecular interactions, the electron-enriched thione group in 4-PT is distinguished to be critical to enabling a strong Pb–S interaction, which not only influences the crystallization paths, but also stabilizes the black-phase CsPbI3 via crystal surface functionalization. The 4-PT based CsPbI3 achieves 13.88% power conversion efficiency in a p–i–n structured device architecture, and encapsulated devices can retain over 85% of their initial efficiencies after 20 days of storage in an ambient environment, which are the best results among fully low-temperature processed CsPbI3 photovoltaics.